Q: Factor x2 plus 6x plus 8?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

(x - 2)(x - 4)

If that's 2x2, the answer is (x + 2)(x2 + 4)

(x-8)(x+8) = x2-64

x2-64 = (x-8)(x+8) when factored

x2+5x-24=0(x+8)(x-3)=0x=-8 x=3

Related questions

x2 + 6x + 8 =(x + 2)(x +4)

-x2 + 6x + 16 = -(x2 - 6x - 16) = -(x - 8)(x + 2) = -(8 - x)(x + 2)

16 + 6x - x2 = 16 + 8x - 2x - x2 = 8*(2 + x) - x*(2 + x) = (8 - x)*(2 + x)

4x+8

(X + 2)(X + 4) Factored

x2 + 2x - 48 = x2 + 8x - 6x - 48 = x(x + 8) - 6(x + 8) = (x - 6)(x + 8)

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

(x - 2)(x - 4)

x2 - 6x - 16 = (x + 2)(x - 8)

(-3,-1)

x3 + 3x2 - 6x - 8 = (x - 2)(x2 + 5x + 4) = (x - 2)(x + 1)(x + 4)

(x + 4)(x + 2)